Local Village Facilitators as Agents of Change Case Study on Community Empowerment in Air Bagi Village, Congcong Subdistrict, Indragiri Hilir Regency - Sitti Rahmah; Virna Museliza; Siti Fatimah (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Assistance is one of the important steps that must be taken to accelerate the achievement of community independence and welfare. Local village facilitators have the main task and function of assisting villages in the administration of village government, inter-village cooperation, the development of village-owned enterprises (BUMDes), and local village-scale development facilities. The village of Air Bagi is still very lacking in community empowerment and organization, as seen from the low level of community enterprise and independence. Therefore, local village facilitators are needed as community facilitators to mobilize and empower the community of Air Bagi village. There is one village facilitator in the Concong sub-district and two local village facilitators, each assigned to assist two villages. The purpose of this study is to examine how local village. facilitators act as agents of change: a case study of community empowerment in Air Bagi Village, Congcong Sub-district, Indragiri Hilir Regency, and the obstacles they face. This study uses a qualitative descriptive method, with data obtained from observations, interviews, and documentation. This research uses a qualitative descriptive method, with data obtained from observations, interviews, and documentation.The results of this study indicate that local assistants in Air Bagi village have not been optimal in providing community empowerment activities in Air Bagi village. This can be seen from the community's dissatisfaction with their performance and the fact that their activities are limited to providing assistance to farmer and fisherman groups. The obstacles encountered are a lack of funding, frequently changing regulations, and the considerable distance to the village.